ETUDE DES PERFORMANCES BOUCHERES DANS LA POPULATION BOVINE LOCALE DANS L’EST ALGERIEN (Sciences & Technologie. C, Biotechnologies, 2007)
The evaluation of performances meat of the local bovine population, allowed us to put down certain values until then unknown. She besides allowed us an approach of the structure of this population intented for butchery and for consumption ; and to determine main characteristics according to age, sex and varieties of this population : mensurations, lively weights, weight of the carcass and output. This work allowed to disclosevery good performances meat of a category of animals,and to offer the ways of improvement and preservation of this population that the qualities of adaptability and rusticity of which are not any more to show.